2020
DOI: 10.1590/1808-1657000292019
|View full text |Cite
|
Sign up to set email alerts
|

Pollination service of Nannotrigona testaceicornis stingless bees in strawberry

Abstract: Strawberry presents moderate dependence on bee pollination service, and pollination is related to the production and quality of fruits. The aim of this study was to evaluate the pollination service provided by Nannotrigona testaceicornis stingless bees in strawberry. Primary flowers of cultivar San Andreas were used in a completely randomized experimental design, with twelve replicates and five types of pollination: one N. testaceicornis visit (1V); two N. testaceicornis visits (2V); three N. testaceicornis vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In cultivars such as 'Oso Grande' and 'Sweet Charlie', Jataí bees (T. angustula) demonstrated pollination effectiveness, in addition to reducing the percentage of deformed fruits, showing an increase in fruit weight (Malagodi-Braga 2018). Thus, like Iraí bees (N. testceicornis), which in the study by Silva et al (2020), visits of bees also provided an increase in weight for the same cultivar as in the present work.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In cultivars such as 'Oso Grande' and 'Sweet Charlie', Jataí bees (T. angustula) demonstrated pollination effectiveness, in addition to reducing the percentage of deformed fruits, showing an increase in fruit weight (Malagodi-Braga 2018). Thus, like Iraí bees (N. testceicornis), which in the study by Silva et al (2020), visits of bees also provided an increase in weight for the same cultivar as in the present work.…”
Section: Discussionsupporting
confidence: 73%
“…Stingless bees have great potential for agricultural pollination, are social, and form perennial and populous colonies with a large flow of activity, not posing risks to human health as they have atrophied stinger (Michener 2007). From these perspectives, stingless bees of the species Iraí (Nannotrigona testceicornis) and Jataí (Tetragonisca angustula) are promising pollinators for different agricultural crops, promoting an increase in fruit production and quality (Malagodi-Braga and Kleinert 2004;Silva et al 2020). In Brazil, some studies with Iraí have been published, for example, on pollination in protected cultivation for cucumber crops (Nicodemo et al 2013;Santos et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, honeybees were better than bumblebees and gave heavier fruit, while in the others, the reverse was true. Silva et al (2020) found that flowers exposed to many insects produced larger fruit than those exposed to single insects. Herrmann et al (2019) exposed plants in cages to orchard bees (Osmia cornuta) or green bottle bees (Luciana sericata).…”
Section: Relationship Between Fertility and The Pollinator Communitymentioning
confidence: 99%